2018
DOI: 10.1049/iet-rpg.2018.5667
|View full text |Cite
|
Sign up to set email alerts
|

Hardware implementation of the fuzzy logic MPPT in an Arduino card using a Simulink support package for PV application

Abstract: The work presented in this study aims to develop an intelligent algorithm, based on fuzzy logic, to track the maximum power point (MPP) of a photovoltaic (PV) panel. Modelling and simulation steps of the PV panel are made by using the MATLAB/Simulink environment, before passing to the description of fuzzy logic MPP tracking (MPPT) algorithm. On an Arduino Mega 2560 controller board, a real-time implementation of the MPPT algorithm by using Simulink Support Package for Arduino Hardware in MATLAB/Simulink was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…This section demonstrates the real‐time feasibility of TVF algorithm using the personal computer (PC) with the MATLAB software and the Arduino Due with a 32 bit Atmel SAM3X8E ARM Cortex‐M3 processor having 512 kB flash memory with 96 kB SRAM and 84 MHz clock speed [49]. The modal voltage signal is extracted from the test system of Fig.…”
Section: Hil Implementation Of Tvf Algorithmmentioning
confidence: 99%
“…This section demonstrates the real‐time feasibility of TVF algorithm using the personal computer (PC) with the MATLAB software and the Arduino Due with a 32 bit Atmel SAM3X8E ARM Cortex‐M3 processor having 512 kB flash memory with 96 kB SRAM and 84 MHz clock speed [49]. The modal voltage signal is extracted from the test system of Fig.…”
Section: Hil Implementation Of Tvf Algorithmmentioning
confidence: 99%
“…Researchers developed various techniques to extract maximum power from the PV sources. Some of the MPPT techniques are perturb and observe (P&O) [5][6][7], hill climbing (HC) [8], incremental conductance (IncCond) [9,10], fractional voltage/current MPPT control [11], fuzzy-logic (FL) [12,13], neural network (NN) [14,15], optimization techniques [16], and sliding mode (SM) control [17][18][19]. Among the conventional MPPT techniques, P&O and the IncCond techniques are widely used due to their simplicity yet being efficient [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Arduino is a microcontroller family and a software creation environment that allows developing programs to interact with the physical world. Due to its agile development capabilities and facility for quick implementation of ideas, many applications have been presented, such as those found in [11][12] [13]. In [11], it was demonstrated that with adaptable Simulink models and a wide number of libraries for the Arduino IDE, the system allows electromyographic (EMG) processing as well as basic classification for actuating both basic hand models and advanced hand prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…All data are evaluated using multivariate data analysis through a customized code written in Matlab. Finally, in [13], an intelligent algorithm is developed, based on fuzzy logic, to track the maximum power point (MPP) of a photovoltaic (PV) panel using Simulink Support Package for Arduino Hardware in MATLAB/Simulink. According to Figure 1, a six-sided dice is an external signal input.…”
Section: Introductionmentioning
confidence: 99%